Resah manusia desa dan kota : sebuah Festschrift untuk Shahnon Ahmad - Siti Hajar Che Man (Siri kecetakan akademik / Penerbit USM, 2010)
Interpretation and criticism on Shahnon Ahmad?s works; festschrift in honor of Shahnon Ahmad, a Malaysian author